Distinguishing the milk microbiota of healthy goats and goats diagnosed with subclinical mastitis, clinical mastitis, and gangrenous mastitis - Polveiro, Richard Costa; Vidigal, Pedro Marcus Pereira; de Oliveira Mendes, Tiago Antônio; Yamatogi, Ricardo Seiti; da Silva, Luciana Saraiva; Fujikura, Juliana Miwa; Da Costa, Mateus Matiuzzi; Moreira, Maria Aparecida Scatamburlo (Frontiers in Microbiology, 2022)
Mastitis, mainly caused by bacterial intramammary infections, is the main problem in the breeding of dairy animals. The inflammations of the mammary gland is separated by types of mastitis, being subclinical, clinical, and the most severe, gangrenous mastitis. Here, we used 16S rRNA amplicon sequencing to characterize the bacterial microbiota of goat milk in the different types of goat mastitis caused by bacteria. We used 72 goat milk samples from a region of the state of Minas Gerais in Brazil, of which 12 were from clinically healthy animals, 42 from animals diagnosed with subclinical mastitis, 16 from animals with clinical mastitis, and 2 from animals with gangrenous mastitis. The group related to gangrenous mastitis was the most divergent in terms of alpha and beta diversity. The most abundant genus among samples of the groups was Staphylococcus spp., and we found a high abundance of Mycoplasma sp. in the milk of animals diagnosed with clinical mastitis. The most statistically relevant microorganisms among the groups were Prevotella sp., Ruminococcaceae, Prevotella ruminicola sp., and Providencia sp. We highlight a new association of bacterial agents in gangrenous mastitis among Escherichia sp./Shigella sp. and Enterococcus sp. and provide the second report of the genus Alkalibacterium sp., in milk samples. Only the taxa Staphylococcus sp., Bacteroides sp., Enterococcus, and Brevidabacterium sp., were present in all groups. The superpathway of L-tryptophan biosynthesis metabolites and the sucrose degradation III (sucrose invertase) pathway were the most prominent ones among the groups. In this study, we demonstrate how a rich microbiota of goat milk from healthy animals can be altered during the aggravation of different types of mastitis, in addition to demonstrating new bacterial genera in milk not previously detected in other studies as well as new associations between agents.